Synthesis of Some New Heterocyclic Compounds Derived from 2-Amino-4-Hydrazino-6-Substituted Pyrimidines - Seada, M.; Abdel-Rahman, R.M.; El-Behairy, M.; Hanafy, Fatin (Asian Journal of Chemistry, 2010)
A number of some new heterocyclic compounds containing 2-amino-6-substituted pyrimidin-4-yl moiety have been synthesized from reaction of 2-amino-4-hydrazino-6-substituted pyrimidines (I c, d) with some condensation cyclization reagents. Their structures have been established on the basis of elemental analysis and spectral data.